Ken Binmore: the Social Contract within the Context of Game Theory - Vasiliauskaitė, Nida (Problemos, 2003)
The article diseusses Ken Binmore's ooneeption of the social contract, which is an attempt to make political philosophy „more scientific“ by means of Rational Choice Theory. Binmore tries to reformulate the fa- mous Rawlsian original position theorem in terms of game theory and for this purposc introduces a strict distinction between personal and cmpathetic preferences. This distinction and that between economic and social time are eriticized for the lack of cleamess and paradoxieal implieations. The aim of the article is to demonstrate that Binmore's conception is not as consistent as it claims to be.
Keywords: social contract; fairness; rationality; game theory